Perancangan Aplikasi Rental Mobil dan Motor Berbasis Web Di Sentosa Abadi Rental - Bimas febriana putra; Febby Alviandi Kurniawan; Muhamad Ilham Qardowi; Sri Mulyati; Niki Ratama (Teknik Informatika Universitas Pamulang, 2022)
Website is a collection of pages that are used to publish information in any form that can be static or dynamic and form a series of interconnected pages that are often called hyperlinks. Vehicle rental is one of the businesses that provides rental services by using a contract or daily rental method, either by releasing the key or with a driver. The type of research methodology carried out is qualitative research, namely research that produces descriptive data in the form of written or spoken words from people and behaviors that can be observed by observing. The Waterfall model is a model that provides a sequential or sequential software lifeflow approach starting from analysis, design, coding, and testing. UML or Unified Modeling Language is a visual modeling method for object-oriented system design tools, or as a language that has become a standard in system visualization, design and documentation.